NOVEL N-HETEROCYCLIC CARBENE SILVER(I) AND GOLD(I) COMPLEXES: SYNTHESIS, STRUCTURAL CHARACTERIZATION, ANTIMICROBIAL STUDIES - Muhand Dohan Abid; Hayder K. Khattar; Hussein Abdulkadhim Hasan; Ali Jabbar Radhi (European Science Publishing, 2025)
In this study, new synthesized bis-benzimidazolium salt that are connected with a 1,2,3-triazol moiety. The proligand of the bis-benzimidazolium-1,2,3-triazole salt as N-heterocyclic carbene (NHC) precursors have been prepared by reacting the initially synthesized 1-octyl-1H-benzimidazole with propargyl bromide in 1:1 molar ratio to produce benzimidazolium salt (2). On the other hand, barbital azide reacted with prepared benzimidazolium salt (2) to obtained proligand bis-benzimidazolium-1,2,3-triazole salt (3). The Au(I) and Ag(I) complexes [M2(nNHC-NHC)2]PF6. FTIR and NMR spectroscopy were used to confirm all of the produced ligands and their complexes. Au(I) and Ag(I) complexes and the generated bis-benzimidazolium salt were tested for their biological activity against a few microbial strains. The substances that were examined demonstrated good activity.
Keywords: N-Heterocyclic Carbenes, Benzimidazolium salts, Ag(I)-NHC, Au (II)-NHC, 1,2,3-Triazole, N‐Heterocyclic–Ag(I) Complexes, Biological Activity.